Trust And Authority In Scholarly Communication In The Light Of Digital Transition: Embedding Practices And The Required Competencies For University Librarians - A. , Abrizah (2015)
Librarians in higher education is not viewed as an academic, but primarily working in a supportive role. This assumption leads to the belief that the role concentrates on information service delivery rather than knowledge creation. A restricted view confining to "support research" denies librarians themselves the chance to realise their capacity to build new knowledge in research. it could instead be asserted that the role of a librarians in higher education is academic and that as information professionals, they have much to offer in scholarly communication. Librarians in academic libraries are increasingly required to "understand" research in order to meet institutional service needs and to further their own careers.